Detection of dendritic cells and related cytokines in follicular fluid of patients with polycystic ovary syndrome. (6th June 2017) - Zhang, Tao; Tian, Fuying; Huo, Ran; Tang, Aifa; Zeng, Yong; Duan, Yong‐Gang
Abstract : Problem: The presence of dendritic cells (DCs) and associated cytokines in follicular fluid (FF) from patients with polycystic ovary syndrome (PCOS) remains unknown. Methods of study: FF was collected from PCOS patients and patients with severe male factor infertility (control) at the day of transvaginal oocyte retrieval. Phenotypes of DC were detected by flow cytometry, and TNF‐α, IL‐6, IL‐10, and IL‐23 were assessed by ELISA. Results: A significant decrease in the percentage of DC was found in patients with PCOS (16.22±5.5%) compared with control (21.27±5.5%, P <.01). E2 on the day of hCG administration was correlated positively with the mean fluorescence intensity of HLA‐DR ( r =.75, P <.01) and reversely correlated with the concentration of TNF‐α in FF ( r =−.69, P <.01). The level of TNF‐α, IL‐6, and IL‐10 increased significantly but IL‐23 decreased in FF from patients with PCOS. Conclusion: The decrease of DC and disturbance of associated cytokines in FF from PCOS patients indicates a disorder of immunological microenvironment of the ovarian follicle, which might be involved in the dysfunction of folliculogenesis.